Coaching across borders: lessons from Finnish high-performance ice hockey coaches - Bespomoshchnov, V. A.; Mallett, C. J.; Saarinen, M.; Vähälummukka, M.; Arvaja, M. (International Sport Coaching Journal, 2025)
Sport coaching has become globalized. Finnish ice hockey is an example of this globalization of a coaching workforce. Indeed, the success of Finnish ice hockey teams in the international arena has been fueling the demand for coaches and players from this country worldwide. Yet, despite the increasing trends of migration of the workforce in sports, there is limited research that is conducted on the experiences of foreign coaches. Thus, in this study, we aimed to expand our understanding of the work of high-performance coaches in the globalized sports context. A case study design was adopted. The participants were 14 Finnish high-performance head coaches with transnational career experiences across 11 nations. Qualitative data were collected via semistructured interviews. Reflexive thematic analysis guided how the authors made sense of these data. Three major themes were (a) preparation practices, (b) acculturation, and (c) emerging learning experiences. The findings provide helpful insights for (a) coach developers when preparing practitioners to work in different cultural settings, (b) club administrators to further inform their decisions when recruiting and working with foreign coaches, and (c) sports` governing bodies to develop policies to support coaches` acculturation in the new country.